Automatic verification of business process integrity. (10th March 2009) - Capel-Tunon, Manuel I.; Mendoza-Morales, Luis E.; Benghazi-Akhlaki, Kawtar
Software engineering methods have shown to be useful in Business Process Modelling (BPM) for improving business-modelling techniques. In this paper, we describe how a Model-Checking (MC) verification technique for software can be integrated with a formal-oriented software design method named MEDISTAM-RT. This is currently used in the development of the Task Model (TM) associated with a Business Process (BP) definition by using UML, enriched with temporal annotations in CSP + T, as the main modelling language. To show a practical use of our proposal, an example of a BPM enterprise-project related to the Customer Relationship Management (CRM) business is discussed.